2020
DOI: 10.17582/journal.aavs/2020/8.11.1211.1219
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ameliorative Effects of Zingiber Officinale and Nigella sativa on Streptozotocin-induced Diabetic Rats

Abstract: Recently, administration of nicotinamide (NA) in a suitable dose before STZ administration was used for experimental induction of type 2 diabetes in rats. Injection of NA leading to partial beta-cells protection from necrosis resulted from STZ injection (Lee et al., 2010). This model may give beneficial tool especially for new insulinotropic agents' investigations (Madkor et al., 2011). The commonly anti-diabetic drug formerly used is metformin. It is used to treat T2DM (Alshathly, 2019). On contrary, hundreds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The present investigation found that STZ caused damage to Langerhans islets and -cells, as evidenced by the loss of their architecture and insulin antibody positivity, which is consistent with prior findings ( EL Baz et al, 2020 , Ibrahim et al, 2020 ). In diabetic rats, both histological and morphometrical evaluations revealed degenerative alterations in pancreatic islets, with a drop in the number of -cells/islet and a decrease in islet area compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The present investigation found that STZ caused damage to Langerhans islets and -cells, as evidenced by the loss of their architecture and insulin antibody positivity, which is consistent with prior findings ( EL Baz et al, 2020 , Ibrahim et al, 2020 ). In diabetic rats, both histological and morphometrical evaluations revealed degenerative alterations in pancreatic islets, with a drop in the number of -cells/islet and a decrease in islet area compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Histologically, only a few samples showed pycnotic changes (early necrosis) in the pancreas. On the contrary, the rest of the tested samples showed an improvement in the number and morphology of islet cells, which were quite normal with a slight interstitial dilation of the blood vessels, and a slight perivascular dilation [ 103 ]. Regarding the glucose tolerance test, the methanolic extract at a dose of 500 mg/kg was able to decrease blood glucose.…”
Section: Pharmacological Properties Of Nigella Sativamentioning
confidence: 99%